A RADIO ANNOUNCER: STRESS LEVEL & PERFORMANCE IMPACT ON RETAILERS INTENTION TO ADVERTISE - Rahmayanti, Rima; Anton Athoillah, Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
The stress level on the Indonesian radio announcer has reached 50–30% for the past two years. Their obligations to connect with a wider public are indeed a challenge, even though it is only known by its voice. In addition, this profession also requires caution with words that are issued when on air. What’s more, the radio broadcasting profession in Indonesia ranks sixth out of the 9 most stressful jobs in 2015. The Indonesian National Private Broadcast Radio Association’s (PRSSNI) state advertising expenditure on radio (Radex) reached 1.2 trillion IDR until the end of the third quarter of 2017. The portion of radio is relatively lower compared to another medium; otherwise, advertising is the biggest revenue for radio. This examination plans to test the effect of radio broadcaster work anxiety on the intention to promote moderate by performance. 50 samples were taken with simple random sampling from consumers in the city of Bandung, Indonesia, that advertise on radio x. Partial Least Square Square (PLS) utilized for data investigation, the results show performance plays an important role in rising or lower impact of work stress level on intention to advertise; this mean performance is proven as a moderating variable, and work stress level impacts positively on intention to advertise.